Dark personality traits and entrepreneurial intentions among Pakistani university students: The role of executive functions and academic intent to entrepreneurship - Khawar, Rabia; Amin, Rizwana; Zulfqar, Asia; Hussain, Samavia; Hussain, Bashir; Muqaddas, Faiqa (Frontiers in Psychology, 2022)
This study examined the mediating role of core Executive Functions (EF: working memory and inhibitory control) and moderating role of Perceived Academic Intent to Entrepreneurship (PAIE) in relationship between Dark Personality Traits (SDT) and Entrepreneurial Intentions (EI) of university students. A sample of 539 university students enrolled in various undergraduate and postgraduate programs completed the Short Dark Triad-3 (SD3), Adult Executive Functioning Inventory (ADEXI) and measures for assessing Entrepreneurial Intent and Perceived Academic Intent to Entrepreneurship. The results showed that of SDT, only Machiavellianism was significantly associated with EI. Both of the core executive functions and PAIE were also positively correlated with EI. Moreover, findings showed that EF positively mediated the relationship between Machiavellian disposition and entrepreneurial intention, while perceived academic intent to entrepreneurship moderated the relationship between executive functions and EI. A significant moderated mediation index was also reported. Findings offer useful insight to the interplay among above mentioned variables and guide educational and organizational psychologists to employ core cognitive strategies for promoting entrepreneurial thoughts and channelizing the productive energies of students with malevolent tendencies through academic coaching.